Assessing the Quality of Metro City Government Financial Report Disclosure - khairudin khairudin; Aminah Aminah; Riswan Riswan; Nurdiawansyah Nurdiawansyah; Erick Surya Dharma (Enrichment : Journal of Management, 2021)
This study is aimed at assessing the quality of disclosure of Metro City LKPD for the period 2014-2018 based on PP No. 71/2010. This research was conducted by comparing the disclosure items made by the Metro City Government with the disclosure items based on PP no. 71/2010. The results of the study found that the LKPD disclosure index by the Metro City Government during the period of receiving WTP opinions was low and the disclosure items that were obeyed were about inventory accounting and items about construction accounting in progress were disclosure items that were often violated. This finding has implications for improving the performance of BPK-RI so that the WTP opinion is given truly describes the real quality of financial management.